The Implementation of School Based Management to Increase Teacher’s Professionalism in Vocational School - Gita Apriani Nur Arofah; Aniek Hindrayani; Jonet Ariyanto (Universitas Sebelas Maret, 2021)
Vocational schools are expected to increase the professionalism of teachers in guiding their students to improve learning achievement. Studying the implementation of School-Based Management by identifying factors influenced in vocational school was one of the ways to find out the answer. With the sample of vocational schools in Karanganyar district, this study used qualitative method to collect the data and by snowball sampling to choose the informant, whose directly involved in the implementation of school based management. The results of this study identified that input, process, and output proved to increase learning performance. Input can be identified from vision, mission, goals, and school targets; process can be identified from constructing planning and program of quality improvement by Strength, Weakness, Opportunity, and Threats (SWOT) analysis; while output can be drawn from evaluating program implementation and formulating new goals. Other side, limited number of teachers who were not accompanied with good understanding about school-based management encourage lower performance.